PENERAPAN SISTEM PAKAR DALAM TES KEPRIBADIAN MYERS BRIGGS TYPE INDICATOR (MBTI) MENGGUNAKAN METODE FORWARD CHAINING - Arlin Ardianensi; Sebastianus A S Mola; Bertha S Djahi (Universitas Nusa Cendana, 2016)
Psychology focuses on learning individual characteristic. Individual characteristic are one factor determining the success of individuals. Most people use IQ as measure of success. However, it has beenfound that EQ (Emotional Quotient) is the most important factor determining the success of individuals.The levels of EQ can be determined using psikotest, which measure individual’s cognitive ability,emotions, inclination of act and things influence that. Myers Briggs type Indicator or MBTI is one of alltest of written test. MBTI have four of dimension that opponent. Although, it is truly everyone have all ofthat character. Therefore, we design an expert system using forward chaining method. This system has100% accurate.